Differential interactions of ToLCNDV with different betasatellites reveal complex viral dynamics in N. benthamiana - Zafar Iqbal; Muhammad Shafiq; Sajed Ali; Mudassar Fareed Awan; Muhammad Farhan Sarwar; Imran Amin; Muhammad Shafiq Shahid; Rob W. Briddon (PLoS ONE, 2025)
Tomato leaf curl New Delhi virus (ToLCNDV), a bipartite begomovirus prevalent in Old World and major cotton-growing regions of Pakistan, has increasingly been found associated with diverse betasatellites. Although betasatellites, small circular DNA satellites, are typically associated with monopartite begomoviruses, they are known to enhance disease severity (pathogenicity), increase viral DNA accumulation, and expand virus host ranges. This study investigated the interaction between ToLCNDV and three widely distributed betasatellites – cotton leaf curl Multan betasatellite strain Multan (Mβ), cotton leaf curl Multan betasatellite strain Burewala (Bβ) and tobacco leaf curl betasatellite (Tbβ) – in Nicotiana benthamiana plants, focusing on the potential emergence of novel viral combinations in cotton-growing regions. Infectious clones of ToLCNDV (either DNA-A [TA] alone or with DNA-B [TB]) were co-inoculated with each betasatellite clone. Results revealed intriguing complexity and variability in interactions: betasatellite with TA/TB affected TB accumulation, suggesting a competition between them, while TA levels increased only in the presence of TB, not apparently with Bβ. Interestingly, Tβ accumulated to the higher levels in plants, followed by Bβ and Mβ, highlighting betasatellite-specific interactions. These findings suggest that ToLCNDV-betasatellite interactions are more intricate than simple antagonism. The co-occurence of ToLCNDV with diverse betasatellites in cotton-growing regions of Pakistan increases the likelihood of the emergence of novel and potentially more pathogenic viral combinations. These intricate interactions have significant implications for understanding the dynamics of CLCuD disease.